Fish oil supplementation improves pregnancy outcomes and size of the newborn: a meta-analysis of 21 randomized controlled trials. (17th June 2016) - Chen, Bing; Ji, Xinran; Zhang, Lei; Hou, Zhaohui; Li, Chundong; Tong, Ying
Abstract: Objective : To observe the effects of fish oil on related pregnancy outcomes. Methods : A systematic search of the Medline, EMBASE and Cochrane's library databases was conducted for the randomized controlled trials published till February 2015 that compared the effects of fish oil supplementation with a control diet in women during pregnancy. Results : Twenty-one studies comprising 10 802 pregnant women were included. Dietary fish oil was associated with a 5.8-day increase in gestational age of the newborn, a 22% reduced risk for early preterm delivery (risk ratio [RR] = 0.78, 95% CI: 0.64–0.95, p  = 0.01) and a 10% reduction in preterm delivery (RR = 0.90, 95% CI 0.81–1.00, p  = 0.05). Fish oil supplementation was associated with higher infantile birth weight (51.23 g), birth length (0.28 cm) and head circumference (0.09 cm), and a 23% lower risk of low birth weight. No benefit from fish oil supplementation was found with regard to risk of intrauterine growth restriction or stillbirth. Conclusions : Dietary fish oil during pregnancy was associated with reduced risk of preterm delivery and improved size of the newborn. Fish oil during pregnancy may be an effective prophylactic for preterm delivery.